Financial Development and Renewable Energy Consumption - Empirical Evidence in Southeast and East Asian Countries - Chien, Nguyen Van (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
Climate change is one of the biggest challenges in our times. Climate change is happening such as rising in temperatures and sea level, drought, the destruction of the ozon layer. Climate change is consistent with a higher level of carbon dioxide that negatively affects human health and the economy. To mitigate the climate change, countries must reduce the emissions linked to the human activities in order to protect the earth safe as well as maintain economic growth in the context of sustainable development. In this case, renewable energy consumption is one of the most effective tools in the form of fighting against climate change. The purpose of the study is to evaluate the impact of financial development on renewable energy consumption in six Southeast Asian countries (i.e. Vietnam, Indonesia, Malaysia, Thailand, and the Philippines) and three East Asian countries (i.e. China, Korea, and Japan). Using the generalized least squares method, the research results confirm that financial development has a negative impact on renewable energy consumption. The research results also find negative effects of inflation and urbanization rates on renewable energy use. Finally, economic growth and lending rates have no impact on renewable energy in the East and Southeast Asian countries.